A Pedagogy of Grace: Love and Care in Edith Stein’s Thought - Guido Cavalli (Paedagogia Christiana, 2025)
The critical comparison with Heidegger’s existential analytics is of utmost importance in Edith Stein’s examination of the structure of the person. Within this framework, the philosopher highlights the necessity of reconsidering human finiteness and temporality as a means of transcending and partaking in the eternal. The fundamentally pedagogical nature of Stein’s thought is shaped by the possibility of attaining fullness and realisation of the essence of human being. The notion of existence itself, regarded as a transformative and educational relationship, enables her to revisit the phenomenological categories of care, anxiety, and freedom. The primary foundation of this pedagogical paradigm, which encompasses the entire ontic framework of the person, lies in the relationship of Grace as a manifestation of divine love.